Política pública de ressocialização pelo trabalho no sistema prisional do Amazonas - Cavalcante, Denis Caetano Gomes (2023)
Seeking to identify the bottlenecks in the Public Policy of Resocialization through Work in the Prison System of Amazonas and the obstacles that prevent it from becoming an instrument of resocialization and an economic-financial tool for the referred State, this research seeks to outline a case study in the System Amazon Prison. Thus, it was up to understand the public policy of work and income and present solutions both for the development of the labor activity of the convicts and the gains to the State of Amazonas and society as a whole. For the proposed objectives, a documental research was carried out, maintaining as base authors researchers such as Cesare Beccaria and Michel Foucault, who exhibit in their studies perspectives on penitentiary work. The search for a solution to the highlighted problem is of great relevance and aims to provide not only scientific enrichment on the topics addressed, but also the optimization of the work carried out in the scope of public administration, directly favoring institutional development and indirectly providing the improvement of the system Amazon public safety.